Keselarasan Penyediaan Nitrogen dari Pupuk Hijau dan Urea dengan Pertumbuhan Jagung pada Inceptisol Darmaga - , Wawan; S. Sabiham; K. Idris; G. Djajakirana; S. Anwar (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2007)
Increasing N use efficiency and decreasing N pollution can be achieved by synchronization between supplying pattern of N and crop N demand. Leaching-incubation experiment had been carried out for evaluating supplying pattern of N from 14 treatments of green manure (Flemingia and Gliricidia), urea and their combinations. Only 5 treatments of the split application of Gliricidia, urea and their combinations, and single application of combination of urea and Gliricidia synchronize with corn N uptake model. These five fertilization treatments were further examined in the greenhouse and in the field experiment. The synchronization between supplying pattern of N and corn growth in treatment without leaching was resulted by application of urea at planting followed by Gliricidia at 3 weeks after planting (WAP) and urea at planting and 3 WAP, whereas in treatment with leaching were resulted by split application of Gliricidia at planting and 3 WAP, urea at planting followed by Gliricidia at 3 WAP, and single application of urea and Gliricidia at planting. Urea applied at planting followed by Gliricidia at 3 WAP resulted in the high production of seed dry-weigh with low N inorganic leaching. Key words: Synchronization, nitrogen, green manure, urea, corn